Smart Energy Efficient Device-to-Multidevice Cooperative Clustering for Multicasting Content. (14th April 2016) - Ashraf, Mateen; Yeo, Woon-Young; Woo, Miae; Lee, Kyung-Geun
A number of nodes that are interested in the same content can be grouped into a cluster and the cluster head can be used to relay the content received from the base station (BS) to the cluster members using device-to-multidevice (D2MD) communication. However, the data rate of such multicast communication depends on the worst channel among the cluster members and the cluster head. The rate can be enhanced by increasing the transmit power; however, this approach may deteriorate energy efficiency (EE) performance of the system. In this paper, we propose transmitting the content from more than one cluster head simultaneously. A novel algorithm is proposed that selects the cluster heads to improve the data rate of the multicast communication while keeping the total transmit power from the cluster heads constant. The cluster members receive power from all the cluster heads within the cluster and hence the received signal to noise power ratio improves. The improved received power makes communication at higher data rates possible, thus reducing the total transmission time. Hence, the energy requirement per bit will reduce. Simulation results show that 19% of reduction in energy per bit is possible by using more than one cluster head within the cluster.